Mind your language: Political discourse affects deforestation in the Brazilian Amazon - Gustavo Magalh\~aes de Oliveira; Jorge Luis Sellare; Jan Börner (University of Bonn, Center for Development Research (ZEF), 2023)
Land users make decisions in an increasingly dynamic environment. Changes in expectations are driven by market and non-market factors, but research on market related drivers of land use change so far dominates in the literature. This paper examines how political discourses affect deforestation rates in the Brazilian Amazon region. Relying on novel data from Twitter, we present the first causal evidence of political discourse on deforestation. Our analysis relies on municipal level monthly panel data for 2019 with alternative remotely sensed measures of forest loss and vegetation fires as outcome variables. The effect of political discourse on these outcomes is identified using a shift-share regression approach. High exposure to laissez-faire political discourses increases forest loss by 2.3-3%, and fires by 2.2%. Our findings are robust across land tenure regimes, varying levels of policy enforcement, and alternative shift-share measures. Moreover, excluding dry season periods from the analysis does not change the main result. Land use in the Brazilian Amazon is highly sensitive to whether, how, and when authorities communicate their will to enforce environmental policy regulations. 'Walking the talk' remains imperative to protect the world's tropical forests, but this study suggests that policy makers must carefully choose their words while walking.
Keywords: Q15; Q56; Q58; 330; political discourse; deforestation; Twitter; Amazon; Brazil